DIVERSITY OF EPIPHYTIC FERN ON THE OIL PALM PLANTS (Elaeis Guineensis Jacq.) IN CAMPUS OF SRIWIJAYA UNIVERSITY INDRALAYA - Harmida, Harmida; Aminasih, Nita; Tanzerina, Nina (BIOVALENTIA: Biological Research Journal, 2018)
Campus of  Sriwijaya University in Indralaya , has a high diversity of flora including fern, especially the epiphytic ferns, whose existence is so widely found in oil palm plants.  Survey about  diversity of this epiphytic has been carried out  from July to November 2017, with aim to identifying the diversity of species of epiphytic ferns in oil palm plants on the campus of UNSRI Indralaya. The research method used is exploration method with direct collection technique from the field and then made herbarium. A total of 27 species of pteridophytes were collected from the study area. Floristic analysis of collected specimens was carried out to find out the families, genus and species. In this survey was  collected 27 species belonged to13 genera, 7 families such  Aspleniaceae, Blechnaceae, Davalliaceae, Lygodiaceae, Nephrolepidaceae, Polypodiaceae, and Vittariaceae. The most common types are Polypodiaceae is Drynaria quercifolia, Drynaria sparsisora, Microsorum pustulatum, Microsorum punctatum, Phymatosorus scolopendria, Polypodium verrucosum, Polypodium polysthicum,  Pyrrosia piloselloides, and Goniophlebium verrucossum. The most widely distributed species in oil palm is Davallia denticulata , Goniophlebium verrucosum, and Nephrolepis biserrata.